2008
DOI: 10.1364/oe.16.019221
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of passively mode-locked soliton erbium waveguide lasers based on slow saturable absorbers

Abstract: We assess the scaling potential of high repetition rate, passively mode-locked erbium-doped soliton lasers. Our analysis focuses on three recently demonstrated lasers using saturable Bragg reflectors (SBR) as the mode-locking element. We use the soliton Area theorem to establish the limitations to increasing the repetition rate based on insufficient intracavity pulse energy, SBR properties, and dispersion engineering. Finally, we examine possible approaches to alleviate these limitations by changing the laser'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…A laser cavity with a net negative GDD is necessary to ensure soliton-like pulse formation that serves as the main pulse-shortening mechanism for high-repetition-rate fiber lasers to generate femtosecond pulses [20]. Recently, Ingmar Hartl et al demonstrated 1.04 GHz Yb-fiber lasers (fully stabilized) using 6 cm gain fiber spliced to a fiber Bragg grating for dispersion compensation [17].…”
mentioning
confidence: 99%
“…A laser cavity with a net negative GDD is necessary to ensure soliton-like pulse formation that serves as the main pulse-shortening mechanism for high-repetition-rate fiber lasers to generate femtosecond pulses [20]. Recently, Ingmar Hartl et al demonstrated 1.04 GHz Yb-fiber lasers (fully stabilized) using 6 cm gain fiber spliced to a fiber Bragg grating for dispersion compensation [17].…”
mentioning
confidence: 99%
“…The composition of the active layer was chosen to provide the maximum refractive index contrast and simultaneously minimal lattice mismatch with the KY(WO 4 …”
Section: Sample Fabricationmentioning
confidence: 99%
“…In most applications, high-performance integrated lasers are required that provide high output power [1] and efficiency [2], excellent beam quality, broad wavelength selectivity [3] and tunability, ultrashort pulses [4], ultra-narrow bandwidth [5], or ultra-low heat generation, potentially by applying a low-cost, straight-forward fabrication process [6].…”
Section: Introductionmentioning
confidence: 99%
“…Various devices have been reported in the literature, including numerous examples of integrated amplifiers [18, 19, 22, 24-26, 30-34, 40, 41, 44, 49-51], lossless power splitters with loss compensation achieved in amplified Er-doped waveguides [43,[58][59][60] and integrated continuous-wave [21,27,29,39,[60][61][62][63][64][65][66][67][68][69][70][71] and mode-locked [28,72] Er-doped lasers. In terms of amplifiers commercial fiber-pigtailed devices have been produced which show gain of 27 dB over a wavelength range of 30 nm [73], making such a device competitive with well-established EDFAs and semiconductor optical amplifier components [74].…”
Section: Integrated Er-doped Optical Amplifiers and Lasersmentioning
confidence: 99%
“…An integrated solution is desired, for combination with other photonic components on the same chip, offering high functionality at low cost. Such on-chip integrated lasers have potential applications in biophotonics, sensing, communications and space, and as femtosecond pulsed sources [72]. In particular, Er-doped waveguide lasers are of interest for their emission at wavelengths around 1.55 µm in the third telecommunication window.…”
Section: Motivationmentioning
confidence: 99%